2021
DOI: 10.3390/ijms22052246
|View full text |Cite
|
Sign up to set email alerts
|

Potential Neuroprotective Mechanisms of Methamphetamine Treatment in Traumatic Brain Injury Defined by Large-Scale IonStar-Based Quantitative Proteomics

Abstract: Although traumatic brain injury (TBI) causes hospitalizations and mortality worldwide, there are no approved neuroprotective treatments, partly due to a poor understanding of the molecular mechanisms underlying TBI neuropathology and neuroprotection. We previously reported that the administration of low-dose methamphetamine (MA) induced significant functional/cognitive improvements following severe TBI in rats. We further demonstrated that MA mediates neuroprotection in part, via dopamine-dependent activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Statistical significance was then determined using Welch’s t-tests between the conditions of interest. Since it has been discussed that the use of multiple testing–corrected false discovery rate maybe too blunt and restrictive for proteomic analysis ( 26 ), especially when analyzing such a heterogeneous and complex tissue as the brain ( 27 , 28 , 29 , 30 , 31 , 32 ), we considered uncorrected p < 0.05 as differentially produced proteins and phosphosites in all our SON and NIL analysis. All data have been deposited at the ProteomeXchange Consortium via the PRIDE partner repository ( 33 ) with the dataset identifier PXD040870 .…”
Section: Methodsmentioning
confidence: 99%
“…Statistical significance was then determined using Welch’s t-tests between the conditions of interest. Since it has been discussed that the use of multiple testing–corrected false discovery rate maybe too blunt and restrictive for proteomic analysis ( 26 ), especially when analyzing such a heterogeneous and complex tissue as the brain ( 27 , 28 , 29 , 30 , 31 , 32 ), we considered uncorrected p < 0.05 as differentially produced proteins and phosphosites in all our SON and NIL analysis. All data have been deposited at the ProteomeXchange Consortium via the PRIDE partner repository ( 33 ) with the dataset identifier PXD040870 .…”
Section: Methodsmentioning
confidence: 99%
“…The result showed that FYT720-NSCS-Exos can availably protect the endothelial barrier and promote the expression of ZO-1 under the hypoxic circumstance. PI3K/AKT pathway is a regulator of apoptosis and survival, and PTEN is considered to be a negative regulator of the PI3K/AKT pathway [47]. p-Akt is a key protein in PI3K/AKT pathway and could inhibit cell apoptosis and improve cell survival [48].…”
mentioning
confidence: 99%